Interaction of HEPES buffer with glass‐ceramic scaffold: Can HEPES replace TRIS in SBF?. Issue 1 (27th November 2016) - Rohanová, Dana; Horkavcová, Diana; Paidere, Laine; Boccaccini, Aldo Roberto; Bozděchová, Pavlína; Bezdička, Petr
Abstract: An international standard (ISO: 23317:2014) exists for the in vitro testing of inorganic biomaterials in simulated body fluid (SBF). This standard uses TRIS buffer to maintain neutral pH in SBF, but in our previous paper, we showed that the interaction of a tested glass‐ceramic material with TRIS can produce false‐positive results. In this study, we evaluated whether the HEPES buffer, which also belongs to the group of Good´s buffers, would be more suitable for SBF. We compared its suitability in two media: SBF with HEPES and demineralized water with HEPES. The tested scaffold (45S5 bioactive glass‐based) was exposed to the media under a static‐dynamic arrangement (solutions were replaced on a daily basis) for 15 days. Leachate samples were collected daily for the analysis of Ca 2+ ions and Si (AAS), (PO4 ) 3‐ ions (UV‐VIS), and to measure pH. The glass‐ceramic scaffold was analyzed by SEM/EDS, XRD, and WD‐XRF before and after 0.3, 1, 3, 7, 11, and 15 days of exposure. Our results confirmed the rapid selective dissolution of the glass‐ceramic crystalline phase ( Combeite ) containing Ca 2+ ions due to the presence of HEPES, hydroxyapatite supersaturation being reached within 24 h in both solutions. These new results suggest that, like TRIS, HEPES buffer is not suitable for the in vitro testing of highly reactive inorganic biomaterials (glass, glass‐ceramics). The ISO standard for such tests requires revision, but HEPES is not a viable alternative to TRIS buffer. © 2016 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 106B: 143–152, 2018.